Economic burden of clinical trials in lung cancer in a German Comprehensive Cancer Center. (June 2017) - Kron, F.; Kostenko, A.; Scheffler, M.; Müller, D.; Glossmann, J.-P.; Fischer, R.; Michels, S.; Nogova, L.; Hallek, M.; Zander, T.; Wolf, J.
Highlights: Lung cancer research has a strong focus on early proof of concept trials. Trials with low patient numbers/investigator-initiated trials are economic risks. There is a need for full cost compensation by pharmaceutical companies. There is a need for novel structures in public funding in precision medicine. Abstract: Objectives: The recent success of individualized lung cancer therapy has triggered fundamental changes in clinical research strategies. To date there is a strong focus on early proof of concept trials in genetically preselected small patient subgroups. This analysis focuses on the economic burden caused by such trials for advanced lung cancer patients in a German Comprehensive Cancer Center (CCC). Methods: The profit margins between recruiting groups with ≤3 and >3 patients were compared. Clinical and economic data from clinical trials for advanced lung cancer (LC), pharma-sponsored trials (PhST) as well as investigator initiated trials (IIT), conducted between 2011 and 2015 at the Center for Integrated Oncology (CIO) Cologne, were analyzed using a profit-center calculation model. Results: 161 patients were enrolled in 27 clinical trials. The key economic parameter determining costs and payments was the 'trial visits'. In comparison of the two groups (A ≤ 3; B > 3 patients enrolled) we found negative profit margins for the low recruiting group (€ −1444). Concerning the number of visits significant differences were found between PhST and IIT (p = 0.009). Additionally, sub-analysis show structural differences in cost composition by conducting PhST and IIT. Conclusion: Trials with low patient numbers and IIT, do not cover the cost. To ensure adequate, cost-covering compensation by pharmaceutical companies CCCs have to thoroughly calculate the cost of early proof of concept trials. The findings of this study also underline the need for novel structures in public funding for investigator-initiated clinical trials in precision medicine.